Meteorological drivers of melt at two nearby glaciers in the McMurdo Dry Valleys of Antarctica - Marte G. Hofsteenge; Nicolas J. Cullen; Jonathan P. Conway; Carleen H. Reijmer; Michiel R. van den Broeke; Marwan Katurji (Journal of Glaciology)
We study the meteorological drivers of melt at two glaciers in Taylor Valley, Antarctica, using 22 years of weather station observations and surface energy fluxes. The glaciers are located only 30 km apart, but have different local climates; Taylor Glacier is generally drier and windier than Commonwealth Glacier, which receives more snowfall due to its proximity to the coast. Commonwealth Glacier shows more inter-annual melt variability, explained by variable albedo due to summer snowfall events. A significant increase in surface melt at Commonwealth Glacier is associated with a decrease in summer minimum albedo. Inter-annual variability in melt at both glaciers is linked to degree-days above freezing during föhn events, occurring more frequently at Taylor Glacier. At Taylor Glacier melt occurs most often with positive air temperatures, but föhn conditions also favour sublimation, which cools the surface and prevents melt for the majority of the positive air temperatures. At Commonwealth Glacier, most of the melt instead occurs with sub-zero air temperatures, driven by strong solar radiative heating. Future melt at Taylor Glacier will likely be more sensitive to changes in föhn events, while Commonwealth Glacier will be impacted more by changes in near coastal weather, where moisture inputs can drive cloud cover, snowfall and change albedo.